Analysis of Society Satisfaction of The E-Toll System In Indonesia Based On Structural Equation Model - M. Fariz Fadillah Mardianto; Rosyida Widadina Ulya; Almira Sophie Syamsudin (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2021)
The implementation of the use of the e-toll system has several evaluations from the community. This evaluation affects community satisfaction with the e-toll system. It is important to know public satisfaction so that the government can evaluate what factors are lacking from the e-toll system so that the service is better. In this study, the method used in the satisfaction analysis is Structural Equation Modeling (SEM). This study uses data based on the results of online questionnaires that have been tested for validity and reliability. In this study, the dimensions of service quality were assessed from the elements of reliability, responsiveness, assurance, empathy and physical evidence. Based on the results of the study, the community is satisfied with the use of the e-toll system on toll roads. However, there are two of the five dimensions of service quality that are very significant, namely the dimensions of reliability and assurance. For this reason, the government needs to pay more attention to reliability and provide guarantees for the e-toll system.